Individual-level and community-level determinants of cervical cancer screening among Kenyan women: a multilevel analysis of a Nationwide survey - Fentanesh Nibret Tiruneh; Kun-Yang Chuang; Peter Austin Morton Ntenda; Ying-Chih Chuang (BMC, 2017)
Abstract Background Studies on the determinants of cervical cancer screening in sub-Saharan Africa have focused mostly on individual-level characteristics of cervical cancer screening. Therefore, in this study, we included both individual- and community-level indicators to examine the determinants of cervical cancer screening among Kenyan women. Methods We analyzed data from the 2014 Kenya Demographic and Health Surveys. Our analysis focused on 9016 married women of reproductive age (15-49 years). We conducted multilevel analyses using generalized linear mixed models with the log-binomial function to simultaneously analyze the association of individual- and community-level factors with cervical cancer screening. Results About 72.1% of women (n = 6498) knew about cervical cancer. Of these women, only 19.4% had undergone cervical cancer screening [58.24% Papanicolaou (Pap) test and 41.76% visual inspection]. Our multivariate analysis results indicated that the prevalence of cervical cancer screening was higher among women aged 35-49 years than women aged 15-24 years. The prevalence was also higher among women residing in the Central, Nyanza, and Nairobi regions than women residing in the Coastal region. Cervical cancer screening was more prevalent among women who had media exposure, had higher household wealth index, were employed, were insured, and had visit a health facility in 12 months than did their counterparts. The prevalence of Pap test history was 19% higher among women who had sexual autonomy than women who did not have sexual autonomy. The prevalence of Pap test history was also higher among communities comprised of higher proportions of women with sexual autonomy and higher education. Conclusions Policies should emphasize increasing gender equality, improving education at the community level, providing employment opportunities for women, and increasing universal health insurance coverage. These focal points can ensure equity in access to health care services and further increase the prevalence of cervical cancer screening in Kenya.